Memetakan Pikiran: Tinjauan Komprehensif tentang Metakognisi dan Fungsi Eksekutif dalam Pembelajaran Sains di Sekolah Dasar - Rafika Putri; Mochamad Nursalim; Diana Rahmasari; Muhammad Rusli; Nurul Mahruzah Yulia; Gemala Qurbani; Ria Alfian Rizkya Putri (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to comprehensively review the development and research trends of metacognition and executive function in elementary science education. The research employed a comprehensive literature review approach to map the evolution, key themes, and future directions in this field. Articles were retrieved from the Scopus and Web of Science databases using the keywords “metacognition,” “executive function,” and “elementary science education,” covering the years 2015-2025. The selection and analysis followed the PRISMA Guidelines, while bibliometric mapping was conducted using VOSviewer software. The findings indicate that metacognition occupies a central position in the global research network and is strongly associated with self-regulation, motivation, and executive function. Three major clusters emerged: (1) theoretical and cognitive foundations of learning, (2) pedagogical and reflective practices in science classrooms, and (3) cross-cultural and contextual applications. The trend shows a shift from conceptual analyses to technology-enhanced and inquiry-based implementations. It can be concluded that strengthening metacognitive-executive abilities promotes students’ critical thinking, cognitive flexibility, and self-regulation, which are essential for 21st-century science education.